Identification of frequency-dependent viscoelastic damped structures using an adjoint method. (4th August 2019) - Hamdaoui, M.; Ledi, K.S.; Robin, G.; Daya, E.M.
Abstract: Viscoelastic parameter identification in sandwich structures (shear modulus and loss factor) is addressed in the present paper. Finite element modelling of three-layered viscoelastic sandwich beams is considered leading to the resolution of a non-linear eigenvalue problem for modal properties determination. An adjoint-based gradient method is developed to minimize the quadratic error between the finite element model and the experimental modal data (frequencies and loss factors). The discrete adjoint approach requires the resolution of a linear system to compute the gradient of the objective function. The method is successfully validated in comparison with central finite difference schemes for gradient's computation. Two use cases are used to illustrate the performance of the method in the case of viscoelastic sandwich beams parameter identification.